Nature Experiences and Adults’ Self-Reported Pro-environmental Behaviors: The Role of Connectedness to Nature and Childhood Nature Experiences - Rosa, Claudio D.; Profice, Christiana Cabicieri; Collado, Silvia (Frontiers in Psychology, 2018)
This cross-sectional study aims to improve our understanding of the psychological pathways behind the commonly reported link between experiences in nature and pro-environmentalism. Particularly, we explore whether nature experiences lead to self-reported pro-environmental behaviors (PEBs) and whether this relation is mediated by connectedness to nature. Additionally, we examine the possible lasting effect of childhood experiences with nature on adults’ PEB. Most studies reporting on the link between contact with nature and pro-environmentalism have been conducted in developed countries, limiting the generalization of the results. To address this gap in the literature, the current study was conducted in a developing country (Brazil) with a sample of 224 young adults. According to our findings, greater contact with nature during childhood is associated with greater contact with nature as an adult, which, in turn, is positively associated with connectedness to nature and PEB. The stimulation of pleasant experiences while in direct contact with nature during childhood seems to trigger interactions with nature in adulthood and consequently, adults embrace pro-environmental actions.